2016
DOI: 10.1111/bju.13461
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of multiparametric magnetic resonance imaging (MRI) results with final histopathology in patients with proven prostate cancer in MRI/ultrasonography‐fusion biopsy

Abstract: ObjectiveTo compare multiparametric magnetic resonance imaging (mpMRI) of the prostate and histological findings of both targeted MRI/ultrasonography-fusion prostate biopsy (PBx) and systematic PBx with final histology of the radical prostatectomy (RP) specimen. Patients and MethodsA total of 105 patients with prostate cancer (PCa) histopathologically proven using a combination of fusion Pbx and systematic PBx, who underwent RP, were investigated. All patients had been examined using mpMRI, applying the Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 19 publications
1
43
0
1
Order By: Relevance
“…As in the current study , use of transperineal biopsy can detect cancer in up to 30% of tumours that would otherwise be missed on extended template TRUS biopsy . Although attempts to reach anterior lesions from the transrectal approach may be feasible , the transperineal approach is felt to provide better sampling in comparison .…”
mentioning
confidence: 55%
“…As in the current study , use of transperineal biopsy can detect cancer in up to 30% of tumours that would otherwise be missed on extended template TRUS biopsy . Although attempts to reach anterior lesions from the transrectal approach may be feasible , the transperineal approach is felt to provide better sampling in comparison .…”
mentioning
confidence: 55%
“…Previous studies also demonstrated that fusPbx showed a better concordance of tumour grading in RP specimen than sysPbx. However, comPbx outperforms fusPbx and sysPbx alone [5,[16][17][18][19]. Based on these data, comPbx should be offered to patients with previous negative sysPbx.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, prospective data are needed to clarify this issue in a re-biopsy cohort as well. Second, we did not perform a direct comparison of mpMRI and whole-mount prostatectomy specimen as previously described [17]. Data of this study are based only on the reported GS of biopsy and RP specimen; however, we performed the comparison in only 41% of patients with proven PCa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that MRI-TRUS image fusion is able to locate the lesion that harbors the highest Gleason grade [10] . Recently, Borkowetz A et al [11] showed that in lesions classified as PI-RADS ≥ 4, significantly more PCa with GS ≥ 7 was detected than in lesions classified as PI-RADS ≤ 3 (90% [77/85] vs. 53% [46/85]; p <0.005). Nevertheless, their work has not explored in great detail the Gleason score 6 (3 + 3), 7 (3 + 4), 7 (4 + 3), and ≥ 8 (4 + 4) according to the PI-RADS scoring.…”
Section: Discussionmentioning
confidence: 99%